Development of a national water‐energy system model with emphasis on the power sector for south africa. Issue 1 (8th January 2018) - Ahjum, Fadiel; Merven, Bruno; Cullis, James; Goldstein, Gary; DeLaquil, Pat; Stone, Adrian
Abstract : A comprehensive archive of information and data pertaining to the development process is available via the Energy Research Data Portal for South Africa. The portal hosts technical reports and data fully describing the model development, estimation of costs and technical parameters; and that of stakeholder engagement for model validation and scenario critique.http://energydata.uct.ac.za/organization/erc-water-energy-nexus © 2018 American Institute of Chemical Engineers Environ Prog, 37: 132–147, 2018